S12-1: An Online Tool to Stimulate Physical Activity for Older People With Dementia – Evaluation and Further Development (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Due to an increase in life expectancy, the number of elderly people with dementia is increasing rapidly. This group largely lives at home, does not have much physical activity (PA), and therefore becomes dependent earlier and requires assistance and care for activities of daily living. In the Netherlands, there are no interventions at a national level for this group.Earlier, an online tool was developed in collaboration with researchers, containing background information, videos, and manuals for use by formal and informal care providers. The tool has been implemented via our broad network of organisations that focus on care and support for the elderly and is widely used since implementation.Project Description: The content and use of the tool has recently been evaluated by means of standardised interviews with professionals from healthcare, welfare, and sports, and with other national organisations that focus on people with dementia. Partly based on these conversations, the tool is being expanded so that it provides a broader picture of aspects that are important, such as more scientific evidence, tools for dealing with dementia, and examples of exercise outside the healthcare sector. The tool is now also suitable for the PA sector and for better use by local policy. The responsibility lies with the latter to enable all elderly people to live at home longer with as little support as possible.The renewed tool is being distributed via the original network of national organisations, now expanded to include stakeholders from municipal policy and the welfare and sports sector.Conclusion: The online tool meets the needs of stakeholders to enable people with dementia living at home to have more PA, thereby promoting physical and mental health and self-reliance.Keywords: Dementia, physical activity, older persons, online tool